Miltochrista wangmini, a new species from China (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Dubatolov, Vladimir V.; Kishida, Yasunori (Zootaxa, 2018)
Miltochrista Hübner, [1819] is one of largest genera of lichen-moths (family Erebidae, subfamily Arctiinae, tribe Lithosiini) including more than 160 valid species, widely distributed in Oriental and Palearctic Regions. For a long time, the genus was treated in a wide sense. Holloway (2001) treated Miltochrista as a small group of species close to the type species of the genus Noctua rubicunda [Denis & Schiffermüller], 1775 (a junior synonym of Miltochrista miniata (J.R. Forster, 1771)), whereas the majority of other Palaearctic and Oriental Miltochrista-like species was assigned to the genera Lyclene Moore in Horsfield & Moore, [1860] and Barsine Walker, 1854. Kirti & Singh (2016) synonymized Lyclene with Miltochrista and at present the genus is treated in wide sense. Nevertheless, Miltochrista in its modern treatment is a heterogeneous group, the status of Lyclene and some other species-groups with significantly different male and female genital structures is unclear, and the generic/subgeneric structure of Miltochrista sensu lato is under revision by Volynkin & Dubatolov (in prep.).